Synthesis and Characterization of a Novel Dapsone-Derived Bisazo Ligand and Its Gold(III) Complex, with Evaluation of Its Antioxidant and Anticancer Activities - Haider Muhammad Hessoon; Hussam Muhammad Abbas (Universitas Gadjah Mada, 2024)
In this study, we successfully synthesized a novel bisazo ligand derived from dapsone and explored its potential as a versatile coordination compound. Furthermore, we formed an Au(III) complex with this bisazo ligand and extensively characterized it using a range of analytical techniques, including UV-visible, FTIR, NMR spectroscopy, mass spectrometry, X-ray diffraction, and thermal analysis (TGA). The Au(III) complex exhibited significant inhibitory effects on liver cancer cells (HEPG2), achieving a maximum inhibition rate of 56.45% at a concentration of 400 µg mL−1. Interestingly, the complex showed comparatively milder effects on normal cells (HDFn). Both the ligand and the gold complex demonstrated antioxidant properties, with ascorbic acid serving as a reference for comparison. These findings underscore the promising potential of the synthesized bisazo ligand and its Au(III) complex in medicinal chemistry, particularly for cancer treatment and antioxidant applications. Additionally, these compounds exhibit nanoscale characteristics, further enhancing their relevance in various scientific and technological fields.